RETRACTED: Association of Self-Leadership With Acute Stress Responses and Acute Stress Disorders in Chinese Medics During the COVID-19 Pandemic: A Cross-Sectional Study - Ji, Rongjian; Zhang, Lan; Ji, Yanbo; Li, Guangzhao; Wang, Renxiu; Xu, Cuiping (Frontiers in Psychiatry, 2022)
Abstract Background: The outbreak of the highly infectious novel coronavirus poses a huge physical and psychological risk to the general public, and to medics, especially. Additionally, self-leadership has been established in improving self-efficacy and modify the tension such as nervousness, depression. So, a cross-sectional survey was conducted to explore the association of self-leadership with ASR and ASD in medics during the COVID-19 epidemic. Methods: Self-reported online questionnaires were used to collected information, 627 participants were included finally. The data were analyzed using univariate analysis, logistical regression model to identify whether self-leadership, sociodemographic and epidemic characteristic were associated with mental health including acute stress responses and acute stress disorders. Results: Front-line medical staff(β=0.338; p＜0.001), the possible of infection of people around you is some (β = 0.141; p＜0.001), subjective estimation of pandemic’s duration is three or six months(β = 0.074; p＜0.05), self-sets(β = -0.022; p＜0.001), self-punishment (β = 0.229; p＜0.001), belief hypothesis and evaluation(β = -0.147; p＜0.05), and successful foresight(β = 0.105; p＜0.05) were statistically significant with acute stress responses. Furthermore, the risk factors accounting for acute stress disorders were marriage(AOR =1.813; 95% CI [1.141, 2.881]; p = 0.012), being a front-line worker (AOR = 25.760; 95% CI [14.220, 46.667]; p＜0.001), visiting Hubei in the last 14 days(AOR = 3.656; 95% CI [1.500, 8.911]; p=0.004), self-punishment(AOR = 1.352; 95% CI [1.180, 1.548]; p＜0.001), and self-dialogue(AOR = 1.256; 95% CI [11.063, 1.483]; p = 0.007). Conversely, having front-line medical staff in one’s family (AOR = 0.523; 95% CI [0.297, 0.923]; p = 0.025), self-sets (AOR = 0.814; 95% CI [0.715, 0.826]; p = 0.002), belief hypothesis and evaluation (AOR = 0.796; 95% CI [0.672, 0.943]; p = 0.038) were protective factors. Conclusions: Self-leadership has potential benefits for acute stress responses or acute stress disorders. Thus, these should be considered by mental health professionals and hospital administrators. Moreover, further clinical follow-up is required to identify any developing PTSD symptoms. And the manuscript mostly treats implications for the field and for society at large an afterthought.